THE CRUCIAL FUNCTIONS OF ECONOMIC INDICATORS: AN OUTLOOK - Singh, Atvir; Anmol (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper examines the crucial function of economic indicators as essential tools for understanding market trends and predicting future performance. Economic indicators include a wide range of metrics, such as GDP growth, unemployment rates, consumer spending, and inflation statistics. By thoroughly analyzing these indicators, analysts and policymakers can gain valuable insights into the overall health of the economy, allowing them to spot patterns, strengths, and weaknesses. This paper highlights the importance of economic indicators in shaping strategic decision-making for businesses, investors, and governments. Through empirical research and theoretical models, it shows how these indicators act as gauges of economic stability, facilitating risk assessment, trend detection, and the development of proactive strategies. A solid grasp of economic indicators provides stakeholders with the foresight needed to effectively navigate ever-changing market environments.